2018
DOI: 10.4066/biomedicalresearch.29-17-3070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enzymatic digestion, cell culture and preservation conditions on surface CD62L expression of primary murine CD3+CD4+ T cells

Abstract: Surface markers are used to identify distinct cell populations. CD62L, a cell adhesion molecule on leukocytes, is used to identify and segregate central memory T (T CM) and effector memory T (T EM) cells. In the present study, we evaluated the effects of experimental conditions on surface CD62L expression of primary murine CD3 + CD4 + T cells. We found that CD62L expression levels were more resistant to collagenase D treatment. Prolonged culture (at 37°C) and preservation (at 4°C) periods resulted in modulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…The incorporation of heat or enzymes to enable this dissociation, however, is almost universal (27). The treatment of tissues with enzymes, heat, or a combination of the two can impact the resulting cell dissociations in ways that may influence conclusions drawn from surrounding research (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of heat or enzymes to enable this dissociation, however, is almost universal (27). The treatment of tissues with enzymes, heat, or a combination of the two can impact the resulting cell dissociations in ways that may influence conclusions drawn from surrounding research (12).…”
Section: Discussionmentioning
confidence: 99%
“…For both methods, single cell suspensions are required as input material for proper staining and analysis and to prevent instrument clogging. While enzyme and heat-based dissociation protocols have often preceded flow cytometry and FACS, recent studies have demonstrated a significant loss of certain immunological cell markers following dissociation with enzymes (12,13). Further, single-cell analysis methods often target rare cell types, making the accurate preservation of varied cell populations and cell markers essential for these applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the combination of mechanical dissociation and collagenase treatment is used, the concentration or incubation time of collagenase should be reduced, since the initial mechanical dissociation would increase the surface area of the tissue, allowing quicker digestion. Unregulated exposure of tissues to collagenase can affect the expression of certain molecules on the cell surface of leukocytes [28,29] ( Figure 2). Similarly, it has also been suggested that enzymatic digestion could alter or damage the T cell receptor (TCR) on T cells [30].…”
Section: Sample Processing and Preparation Of Single-cell Suspensionmentioning
confidence: 99%
“…In addition, animal-based enzymes were found to decrease the expression levels of proteins related to growth and metabolism, and to increase the expression levels of proteins related to apoptosis. Liu et al found that the use of trypsin detachment could also affect the autoimmune function of primary cells [ 22 ].…”
Section: Introductionmentioning
confidence: 99%